Variations of Biochemical Parameters of Some Selected Vegetables Under Different Preservation Techniques - Shatee, Z S; Brahma, P P; Biswas, P; Bhuiyan, M J H; Farukh, M A (Journal of Environmental Science and Natural Resources, 2025)
The present study was conducted to examine variations in the biochemical properties of selected vegetables under different storage conditions. The vegetables analyzed included spiny gourd, pointed gourd, snake gourd, sponge gourd, and Chinese okra. The biochemical parameters measured were moisture content, vitamin C, titratable acidity, total sugar, and reducing sugar. Among the control samples, sponge gourd had the highest moisture content (94.36%), while spiny gourd contained the highest vitamin C (6.72 mg/100 ml). Sponge gourd also exhibited the highest titratable acidity (7.28%). Pointed gourd had the highest total sugar content (0.25 mg/ml), whereas sponge gourd recorded the highest reducing sugar content (0.61 mg/ml). Freshly collected vegetables were stored in both airtight and perforated polyethylene bags under normal and refrigerated conditions. Air exposure and temperature were key factors influencing storage conditions. Quality parameters were assessed in fresh vegetables and at 48-hour intervals during storage. The recorded data were analyzed using analysis of variance (ANOVA), and the means of different parameters were compared using the least significant difference (LSD) test. The results revealed significant variations among treatments in terms of moisture content, vitamin C, titratable acidity, total sugar, and reducing sugar. All quality parameters were compared against the control samples. Environ. Sci. & Natural Resources, 14(1&2): 45-48, 2025